ISTRAŽIVANJE UTICAJA BRENDA POSLODAVCA NA KONKURENTNOST U HOTELSKOJ INDUSTRIJI - Ognjanovic, Jasmina M. (International Journal of Economic Practice and Policy, 2021)
Human resources are one of the key resources for gaining and maintaining the competitive advantage of hotels, so increasing the value of human capital becomes a priority for hotel management. One way to increase the value of human capital is to build an employer brand in the hotel industry. The paper aims to examine the relationship between employer brand and competitiveness in the hotel industry. The obtained research results indicate the importance of the following five dimensions of the employer brand: organizational culture, work-life balance, the attractiveness of the hotel, corporate social responsibility, opportunities for training, development and advancement of employees. Results of correlation analysis indicate a positive, significant correlation between employer brand dimensions, while the regression analysis results support the impact of the hotel’s employer brand on competitiveness. Corporate social responsibility has a significant impact on competitiveness as one of the dimensions of an employer brand.